Development of Anatomy Web-Based Assessment based Augmented Reality (AR) - Hasibuan, Sanusi; Azmin, Chairul; Nasution, Muhammad Faisal Ansari; Chairad, Muhammad (Journal of Education, Health and Sport, 2022)
The main objectives of this study are to describe the development design of the Augmented Reality (AR) based Anatomy web-based assessment, to describe the implementation of the Augmented Reality (AR) based Anatomy web-based assessment development, and to describe the teacher’s response to the use of Augmented Reality (AR) based Anatomy web-based assessment. The research was conducted at the State University of Medan. This web-based assessment development design is based on the Borg & Gall research and development (R&D) stage pattern as adopted by Sugiyono. As for the product design model, this web-based assessment follows the ASSURE model. The results of this study indicate that the product developed, namely web-based assessment, has gone through design and testing and revision, so the product is declared suitable for use. Students also gave a good response, namely 92% of the use of the web as an assessment tool equipped with Augmented Reality (AR)-based animation.